2019
DOI: 10.1021/acs.jpclett.9b01753
|View full text |Cite
|
Sign up to set email alerts
|

Proteins are Solitary! Pathways of Protein Folding and Aggregation in Protein Mixtures

Abstract: We present a computational and experimental study on the folding and aggregation in solutions of multiple protein mixtures at different concentrations. We show how in protein mixtures, each component is capable of maintaining its folded state at desensitises higher then the one at which they would precipitate in single species solutions. We demonstrate the generality of our observation over many different proteins using computer simulations capable of fully characterising the cross-aggregation phase diagram of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 39 publications
2
46
2
Order By: Relevance
“…The results presented here have a profound implication on the physiology of the cell where protein aggregation is a fundamental parameter for expression regulation . Using the results obtained in this work, we have shown that indeed that proteins can be optimised to fold and regulated independently of the other proteins . In other words, provided that each protein does not pass their aggregation threshold concentration (counting only that particular species and not the total protein concentration), cross interactions do not affect the folding and the aggregation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results presented here have a profound implication on the physiology of the cell where protein aggregation is a fundamental parameter for expression regulation . Using the results obtained in this work, we have shown that indeed that proteins can be optimised to fold and regulated independently of the other proteins . In other words, provided that each protein does not pass their aggregation threshold concentration (counting only that particular species and not the total protein concentration), cross interactions do not affect the folding and the aggregation.…”
Section: Discussionmentioning
confidence: 99%
“…Here we present a computational study on the folding, stability and aggregation of proteins optimised according to the environment. We consider a series of native protein structures, and for each, we determine one or more sequences designed to make the protein fold into the aqueous environment . Each sequence exhibits a different ratio between the number of hydrophilic amino acids exposed to the solvent and the number of hydrophobic amino acids buried into the core of the protein in its native conformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first evidence to support our claim comes from our previous work on heteropolymer design including the Caterpillar design Our work on design showed that provided that a heteropolymer chain is designable (we defined the rules to identify such property) then the 3D structures can be designed with high accuracy independently of the interaction matrix used to define the amino acid interactions . In fact, the same design strategy works for lattice and off‐lattice proteins with implicit or explicit solvent, plus the above mentioned patchy polymers . This result is the first indications that the key correlations that determine the folding do not depend on the particular model used to represent the residue interactions.…”
Section: Methodsmentioning
confidence: 99%
“…This result is the first indications that the key correlations that determine the folding do not depend on the particular model used to represent the residue interactions. The only requirement, of course, is that the protein structural space is correctly represented and for that, we can bring not only the evidence produced by the Caterpillar model it‐self but also made with its close cousins: the tube model of Maritan et al . and the CamTube model .…”
Section: Methodsmentioning
confidence: 99%